WAVE PROPAGATION ON A FLUME: PHYSICAL MODELLING - Conde, J. M. (2013)
The knowledge of wave transformation and breaking characteristics near coastline is essential for the nearshore hydrodynamics and the design of coastal structures. This paper describes a wide range of wave flume tests performed at the National Laboratory for Civil Engineering (LNEC), located in Lisbon (Portugal), which main objective was to study wave shoaling and breaking over a set of different gentle slopes for several incident waves and thus to contribute for a better understand of the hydrodynamics of wave transformation. The experimental conditions, the measurement equipment, the incident wave characteristics, the type of measurements performed (free surface elevation and particle velocity) and the data obtained are described. Time and spectral analysis based upon the measured data are also performed and presented. For a regular wave with a period of 1.5s and a height of 0.1m are presented and discussed the following results: free surface elevation at selected sections along the flume; the spectral analysis; the significant wave height and average period along the flume; the particle velocity components at different locations along the flume; the average, maximum and minimum values of the longitudinal component of the velocity along the flume; the two dimensional distribution of the three components of the velocity; and longitudinal velocity component vertical profiles.